An Integrative Model of Cultural Intelligence and Empathy for Intercultural Communication with Recent Immigrants in Healthcare Contexts - Hussein, Mariam Mohamed Ahmed Magdy (Université d'Ottawa / University of Ottawa, 2023)
In our increasingly interconnected world, intercultural communication has gained paramount significance, particularly in contexts characterized by unprecedented cultural diversity, such as healthcare settings. The influx of newcomers from diverse cultural backgrounds necessitates effective intercultural communication, yet this challenge remains uncharted. Nonverbal behaviours, a key communication component, also remain understudied despite their significant cultural variation and influence on the perception of effective communication. Thus, healthcare professionals face the challenge of navigating intricate cultural norms and communication styles without evidence-based guidelines. This dissertation seeks to unravel the interplay between cultural intelligence and empathic communication through three papers exploring the communication recipient's perspective, nonverbal behaviours' role, and the communication senders' implications. The findings challenge the previous focus on empathy senders and highlight the role of empathy recipients. Nonverbal cues are recognized as pivotal in communication, and culture plays a significant role in interpreting these cues, influencing how empathy is conveyed across cultural boundaries. The dissertation's significance extends beyond healthcare, offering valuable insights for policymakers, international managers, and individuals engaged in intercultural interactions. Education on culturally specific nonverbal cues can enhance self-awareness and improve the capability to provide empathic services to clients from diverse cultural backgrounds. In conclusion, this dissertation is a substantial stride forward in understanding intercultural communication within healthcare, emphasizing the importance of empathy, cultural intelligence, and nonverbal communication. Recognizing cultural differences in nonverbal cues and fostering cultural competence is crucial for healthcare providers to improve patient experiences and their quality of care.
Keywords: Empathy; Cross-cultural communication; Immigrant populations; Inclusion; Cultural Intelligence